USP9X controls translation efficiency via deubiquitination of eukaryotic translation initiation factor 4A1. Issue 2 (8th December 2017) - Li, Zengxia; Cheng, Zhao; Raghothama, Chaerkady; Cui, Zhaomeng; Liu, Kaiyu; Li, Xiaojing; Jiang, Chenxiao; Jiang, Wei; Tan, Minjia; Ni, Xiaohua; Pandey, Akhilesh; Liu, Jun O; et al.
Abstract: Controlling translation initiation is an efficient way to regulate gene expression at the post-transcriptional level. However, current knowledge regarding regulatory proteins and their modes of controlling translation initiation is still limited. In this study, we employed tandem affinity purification and mass spectrometry to screen for unknown proteins associated with the translation initiation machinery. Ubiquitin specific peptidase 9, X-linked (USP9X), was identified as a novel binding partner, that interacts with the eukaryotic translation initiation factor 4B (eIF4B) in a mRNA-independent manner. USP9X-deficient cells presented significantly impaired nascent protein synthesis, cap-dependent translation initiation and cellular proliferation. USP9X can selectively alter the translation of pro-oncogenic mRNAs, such as c-Myc and XIAP. Moreover, we found that eIF4A1, which is primarily ubiquitinated at Lys-369, is the substrate of USP9X. USP9X dysfunction increases the ubiquitination of eIF4A1 and enhances its degradation. Our results provide evidence that USP9X is a novel regulator of the translation initiation process via deubiquitination of eIF4A1, which offers new insight in understanding the pivotal role of USP9X in human malignancies and neurodevelopmental disorders.